The Development of Mathematical Reasoning and Creativity Thinking Abilities for Grade 12 Students Using Project – Based Learning with Cooperative Learning LT Technique - Jongkolnee Dejporn; Bhiasiri, Dr.Siribhong (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2022)
This research aims to develop Mathematical reasoning and creativity thinking abilities using project-based learning with cooperative learning LT technique for Grade 12 Students which has criterion 70% or above of students’ average score and at least 70% of the students reach the criterion, and to examine the students’ satisfaction. Target group is grade 12 students for 29 students. This action research includes 3 cycles. The research found that; 1) The average score of Mathematical reasoning ability is 70.43% and 82.76% passed the criterion which is above the criterion. 2) The average score of Mathematical creativity thinking ability is 77.33% and 86.21% reached the criterion that is above the criterion. and The students were satisfied at average score of 4.68 which is the highest level.